The 123s of ABC in SAP : using SAP R/3 to support activity-based costing - Sedgley, Dawn J. (Wiley, 2001)
Given SAP's dominance in the enterprise resource planning (ERP) market, many companies and their managers encounter SAP AG applications in some form or another. Many of these organizations have recognized the value of utilizing Activity-Based Costing/Management concepts to perform more accurate cost assignments or drive performance initiatives. Managers are then faced with trying to determine how Activity-Based Costing can be incorporated into the SAP environment. The 123s of ABC in SAP is the first book of its kind designed to help business managers understand the capabilities of the SAP R/3.